Fatty Acids Profile, Oxidative and Hydrolysis Stability of Virgin Coconut Oil and Palm Stearin Based Human Milk Fat Analog - Karouw, Steivie; Suparmo; Hastuti, Pudji; Utami, Tyas (International Coconut Community, 2014)
The objectives of the research are to evaluate fatty acids profile, oxidative and hydrolysis stability of human milk fat (HMF) analog by using virgin coconut oil (VCO) and palm stearin as raw materials. The HMF analog was synthesized through enzymatic interesterification catalyzed by lipase from Rhizomucor miehei. The fatty acid profiles of interesterification products were monitored using gas chromatography. Oxidative stability test was carried out for up to 72 hours at 60oC. The peroxide value was measured during 0, 24, 48 and 72 hours of storage duration. Hydrolysis stability test was held for up to 8 days at room temperature. The free fatty acid content was monitored during 0, 2, 4, 6 and 8 days of storage. The results showed that the resulted HMF analog having high percentage of palmitic acid in the sn-2 position, similar to that of HMF. The palmitic acid content in the sn-2 position was around 39.71%. The MCFAs were esterified in the sn-1 and sn-3 position and the main fatty acid constituent was lauric acid of 39.37%. The obtained HMF analog was stable to oxidative and hydrolysis deterioration as indicated by the peroxide value and free fatty acid content during storage.